Relationship between work environment and job performance of community development (2020)
The job performance of community development officers is a key factor to the success of community development activities in LGAs. However, declining performance of community development officers in LGAs in Nigeria has become a source of concern and in fact, a major challenge of human Service organisations. In view of this, the study investigated relationship between work environment and job performance of community development officers in Akinyele Local Government Area, Oyo State. The correlational survey design was adopted and a simple random sampling technique was used to select a total of four hundred and thirty-seven respondents for the study. Two structured questionnaires; Work Environment Scale (WES) with a reliability coefficient of 0.82 and Job Performance Scale (JPS) with a reliability of 0.84 were the main instruments used for data collection. Three hypotheses were tested using Pearson Product Moment Correlation (PPMC) and multiple regression analysis. The study showed that autonomy (r= .067, p< 0.05), work pressure (r= .071, p< 0.05) and physical comfort (r= .069, p<0.05) had significant correlation with job performance of community development officers in Akinyele Local Government Area of Oyo State. It was therefore recommended that the work environment should be made conducive to workers so that they can perform optimally. Officers should be given responsibilities backed up by commensurate authority